Effect Of Deltamath Towards Students Learning Outcome: A Study Case In South Tangerang - Muhammad Agustiuddin (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The advance of technology has affected many aspects of people’s lives. One field that also has been greatly affected by this advancement is Education. There are lots of online learning platforms that emerged in the past 2 decades. Khan Academy and IXL are two favourite examples of those platforms that are being used to help students learning Mathematics and Science. DeltaMath, although not as famous, is also of the platforms that are available and can be used to help students learning Mathematics. This study examined the impact of DeltaMath toward students’ Mathematics learning outcomes. There are 56 samples in total that are divided into 2 group of 28 students. One group is the group of students who are introduced to and are using DeltaMath as supplementary resources in their learning and the other group consisted of students that didn’t use the DeltaMath in their learning. Main findings show that: 1. The average score of the final exam of group who used DeltaMath is higher than the group of students that didn’t use DeltaMath. 2. Students who solved more than 150 questions in DeltaMath performed better in the final exam than most students, their average is 7 points higher compared to the average of all students. 3. There is no significant difference between group that are using DeltaMath compared to group of students who didn’t use DeltaMath. There are still few publications related to DeltaMath, unlike Khan Academy and IXL, thus, this study hopefully can contribute to the research of the impact of using DeltaMath.